1994
DOI: 10.1111/j.1600-051x.1994.tb00737.x
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding on probing. A parameter for monitoring periodontal conditions in clinical practice

Abstract: The present study is a follow-up report on the use of bleeding on probing (BOP) as a clinical indicator for disease progression or periodontal stability, respectively. Following active periodontal therapy, 39 patients were incorporated in a program of supportive periodontal therapy for a period of 53 months with recall intervals varying between 2-8 months. The patients received supportive therapy 7 to 14 x. At the beginning of each maintenance visit, the tissues were evaluated using BOP. Reinstrumentation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
172
0
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 216 publications
(192 citation statements)
references
References 11 publications
9
172
0
11
Order By: Relevance
“…32 In another study that evaluated the use of bleeding on probing as an indicator for periodontal disease progression or disease stability, the majority of patients who experienced disease progression demonstrated a mean BOP score of greater than or equal to 30%. 33 On the other hand, individuals with BOP score less than or equal to 20% exhibited a significantly lower risk for further attachment loss. Moreover, a retrospective study reported that patients with 16% or more BOP sites were more likely to experience further periodontal breakdown during the maintenance phase of periodontal therapy.…”
Section: Discussionmentioning
confidence: 96%
“…32 In another study that evaluated the use of bleeding on probing as an indicator for periodontal disease progression or disease stability, the majority of patients who experienced disease progression demonstrated a mean BOP score of greater than or equal to 30%. 33 On the other hand, individuals with BOP score less than or equal to 20% exhibited a significantly lower risk for further attachment loss. Moreover, a retrospective study reported that patients with 16% or more BOP sites were more likely to experience further periodontal breakdown during the maintenance phase of periodontal therapy.…”
Section: Discussionmentioning
confidence: 96%
“…BOP has been used an objective inflammatory parameter for the evaluation of periodontal conditions. A BOP prevalence of 25% has been considered the cut-off point between patients with maintained periodontal stability and patients with recurrent disease [52]. Studies of Claffey et al [53] and Badersten et al [54] revealed further evidence of BOP percentages between 20% and 30% determining a higher risk for disease progression.…”
Section: Discussionmentioning
confidence: 97%
“…15,16 This parameter is associated with the presence of biofilm and subgingival calculus, 17 and has been used to indicate the need for subgingival intervention. 18,19 During periodontal maintenance, BoP and probing pocket depth (PPD) are used as prognostic factors for future periodontal disease activity. 20 The absence of BoP has been shown to be a good indicator of stable CAL, and its presence has a moderate predictive value for future attachment loss.…”
Section: Declaration Of Interestsmentioning
confidence: 99%